2008
DOI: 10.1002/elps.200800172
|View full text |Cite
|
Sign up to set email alerts
|

Electrokinetic sample injection for high‐sensitivity capillary zone electrophoresis (part 1): Effects of electrode configuration and setting

Abstract: Electrokinetic injection (EKI) is usually considered as one of the useful approaches to improve sensitivity of CZE analysis. In the present study, we explored the relationship between electrode position and sample amount injected during EKI process by using 2D computer simulation (CFD-ACE+) and real experiments, aiming to obtain higher detection sensitivity. Two different models of electrode configuration, a capillary inserted in a hollow electrode and a capillary surrounded by a cylindrical electrode on the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 18 publications
(23 reference statements)
2
43
0
Order By: Relevance
“…Refs. [105][106][107][108][109][110][111]) open the possibility to simulate new and more complex problems that occur under the influence of an electric field. This is particularly useful for chip-based instrumentation in which channels of various dimensions, curvatures and intersections are being employed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refs. [105][106][107][108][109][110][111]) open the possibility to simulate new and more complex problems that occur under the influence of an electric field. This is particularly useful for chip-based instrumentation in which channels of various dimensions, curvatures and intersections are being employed.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the dynamic models referred to above, this approach is based upon the modeling of the trajectories of each individual molecule, requires extremely powerful computers in order to compute the motion of a statistically significant number of molecules and is not further considered in this review. Other theoretical work absent from this review includes (i) a stochastic model describing the consequences of wall adsorption in CE [84], (ii) the temperature-dependent interconversion models of dynamic electrophoresis [85][86][87][88], (iii) the simulation model for electroinjection analysis and electrophoretically mediated microanalysis [89], (iv) the affinity electrophoresis models of Andreev et al [90] and Fang and Chen [91][92][93][94], which describe affinity interactions in CE under simplified electromigration conditions, (v) the models of Cann and coworkers describing interacting systems in ZE [95], MBE [96] and IEF [97][98][99], (vi) the models predicting analyte separation in CEC [100][101][102][103][104], (vii) all multi-dimensional models that describe electrokinetically driven mass transport and separations in microfabricated chip devices, such as those of Ermakov et al [105], Bianchi et al [106], Chatterjee [107], Sounart and Baygents [108], Datta and Ghosal [109] and Hirokawa et al [110], (viii) the model of electrokinetic sample injection for capillary CZE with consideration of the electrode configuration [111], (ix) the models that predict sample zone formation, distortion and solute separation in continuous flow electrophoresis [112,113] and recycling electrophoresis [114][115][116], (x) the models describing off-gel electrophores...…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to ascertain the optimum injection time for a water plug, since the sensitivity and reproducibility were reportedly improved by injecting the water plug into the capillary. 10 Hirokawa et al 37 described the effectiveness of prolonging the vertical distance between the tip of electrode and the capillary end (Dec) to obtain high sensitivity in EKS-CZE. The amount of sample injected into the capillary can be increased by extending Dec.…”
Section: Strategy For Separation and Sensitivity Enhancementmentioning
confidence: 99%
“…The analytical conditions, time of water plug injection, time, and voltage of sample introduction were examined and optimized. Boer and Ensing, 36 and Hirokawa et al 37,38 reported that the efficiency of EKI and EKS is strongly related to the electrode configurations. Therefore, we investigated the effects of the distance between the tip of the electrode and a capillary end (Dec) on the peak heights for the analytes listed above using FASI.…”
Section: Introductionmentioning
confidence: 99%
“…As described in our recent related study [9], the efficiency of EKI is strongly related to the electrode configuration and setting, and the injected sample amount can be increased over ten times by prolonging the distance between an electrode and a capillary end (D ec ). In this way, EKS-CZE could be efficient enough to achieve 20 ppt LOD for rare earth elements only by increasing D ec from the default value of 1.1 to 19.5 mm (at EKI 250 s).…”
Section: Introductionmentioning
confidence: 98%